2017
DOI: 10.21037/gs.2017.03.10
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic versus open 1-stage resection of synchronous liver metastases and primary colorectal cancer

Abstract: According to the results, in patients, whose primary colorectal cancer and metastatic liver disease was amenable to a minimally invasive resection, a concomitant laparoscopic approach resulted in less morbidity without compromising oncologic outcomes. This suggests that a laparoscopic approach may be considered in appropriate patients by surgeons with experience in both advanced laparoscopic liver and colorectal techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 21 publications
(27 reference statements)
1
31
0
Order By: Relevance
“…In contrast, one study noted shorter operative times for the laparoscopic group ( P < 0.05) . EBL was lower in the LSR group compared with the OSR group in four studies ( P < 0.05), while the other four studies reported no difference in EBL between OLR and LSR . Two cases of conversion from laparoscopic to open approach were reported.…”
Section: Resultsmentioning
confidence: 86%
See 4 more Smart Citations
“…In contrast, one study noted shorter operative times for the laparoscopic group ( P < 0.05) . EBL was lower in the LSR group compared with the OSR group in four studies ( P < 0.05), while the other four studies reported no difference in EBL between OLR and LSR . Two cases of conversion from laparoscopic to open approach were reported.…”
Section: Resultsmentioning
confidence: 86%
“…Postoperative morbidity was 19.9% (n = 27/136) in the LSR group compared with 32.8% (n = 56/171) in the OSR group. There were no differences in the incidence of complications among patients undergoing LSR versus OR except for the study by Gorgun et al that noted higher overall complications in the OSR group ( P = 0.016). Only two comparative studies included classification of postoperative complications according to the Clavien‐Dindo system (Table ) .…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations